Research on the Level of Production Traumatism and Professional Sickness in the Field of Animals Husbandry of Agrarian and Industrial Complex of Ukraine - Савченко, Л. Г.; Цивенкова, Н. М.; Савченко, В. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
This paper studies the level of occupational injuries and professional sickness in the field of animals’ husbandry and processing products of animals’ husbandry of agrarian and industrial complex of Ukraine. The analysis of the types of diseases associated with livestock and the structure of injuries of professional staff in the field is given in the paper. An initial allocation of identified occupational diseases and poisoning effect on the duration of working main adverse factors are shown. Thus; the main cause of injury to workers is a violation of the labor process; that access to work without instruction; without training; lack of labor protection instructions; and more. These data are forced to pay attention primarily on the need to respect the technological and labor discipline; to improve the professional level of safety requirements when working with machinery and equipment; with service animals to address the causes and sources of injury; to improve the quality of training and certification of staff and increased rigor in the evaluation.